CONTEMPORARY PROBLEMS OF RESEARCHING SMART - Aleksey M. Karmanov; Mikhail V. Karmanov (Статистика и экономика)
In recent years increasing attention is paid to SMART as special areas for development, which plays a crucial role in life of modern society. In this regard, systematization of problems associated with the penetration process of smart innovative technologies in various spheres of human activity has great scientific and practical significance.